Protein expression in the brain of rat offspring in relation to prenatal caloric restriction. (17th August 2016) - Aravidou, Eftychia; Eleftheriades, Makarios; Malamitsi-Puchner, Ariadne; Anagnostopoulos, Athanassios K.; Aravantinos, Leon; Dontas, Ismene; Aravidis, Christos; Creatsas, Georgios; Tsangaris, Georgios; Chrousos, Georgios P.
Abstract: Objective : Intrauterine growth restriction (IUGR) has been associated with decreased supply of crucial substrates to the fetus and affects its growth and development by temporarily or permanently modifying gene expression and function. However, not all neonates born by calorie restricted mothers are IUGR and there are no reports regarding their brain protein expression vis-à-vis that of their IUGR siblings. Here, we investigated the expression of key proteins that regulate growth and development of the brain in non-IUGR newborn pups versus IUGR siblings and control pups. Methods : Rat brain proteins were isolated from each group upon delivery and separated by two-dimensional gel electrophoresis (2-DE). Results : 14-3-3 Protein, calreticulin, elongation factor, alpha-enolase, fascin, heat-shock protein HSP90 and pyruvate kinase isozymes were significantly increased ( p  < 0.05) in samples obtained from IUGR newborn pups compared to non-IUGR. Conversely, collapsin response mediator proteins, heat-shock70 and peroxiredoxin2 were decreased in IUGR group compared to non-IUGR. Conclusions : In our experimental study, IUGR pups showed an altered proteomic profile compared to their non-IUGR siblings and non-IUGR controls. Thus, not all offspring of calorie-restricted mothers become IUGR with the accompanying alterations in the expression of proteins. The differentially expressed proteins could modulate alterations in the energy balance, plasticity and maturation of the brain.